2023
DOI: 10.5271/sjweh.4086
|View full text |Cite
|
Sign up to set email alerts
|

The impact of occupational exposures on infection rates during the COVID-19 pandemic: a test-negative design study with register data of 207 034 Dutch workers

Abstract: OBJECTIVE: This study aimed to investigate the effects of occupational exposures on the risk of a positive COVID-19 test, and whether this differed across pandemic waves. METHODS: Data from 207 034 workers from The Netherlands with test data on COVID-19 from June 2020 until August 2021 were available. Occupational exposure was estimated by using the eight dimensions of a COVID-19 job exposure matrix (JEM). Personal characteristics, household composition and residence area were derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The brief 4-item Patient Health Questionnaire (PHQ-4), combining the 2-item PHQ-2 and the 2-item Generalized Anxiety Disorder (GAD)-2 scales, was used to rate mental distress in terms of depression and anxiety symptoms at t3 and t4. PHQ-4 scores were categorized as normal (0-2), mild (3)(4)(5), moderate (6)(7)(8), and severe (9)(10)(11)(12), whereas a score greater than or equal to 3 on the 0-to-6-point PHQ-2 and GAD-2 subscales indicated a probable major depressive disorder or a probable generalized anxiety disorder, respectively [25,26]. Work-privacy conflicts were surveyed at t3 and t4 analogous to the German version of the Copenhagen Psychosocial Questionnaire (COPSOQ) using the question "To what extent do the demands of your work interfere with your private and family life?"…”
Section: Follow-up Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…The brief 4-item Patient Health Questionnaire (PHQ-4), combining the 2-item PHQ-2 and the 2-item Generalized Anxiety Disorder (GAD)-2 scales, was used to rate mental distress in terms of depression and anxiety symptoms at t3 and t4. PHQ-4 scores were categorized as normal (0-2), mild (3)(4)(5), moderate (6)(7)(8), and severe (9)(10)(11)(12), whereas a score greater than or equal to 3 on the 0-to-6-point PHQ-2 and GAD-2 subscales indicated a probable major depressive disorder or a probable generalized anxiety disorder, respectively [25,26]. Work-privacy conflicts were surveyed at t3 and t4 analogous to the German version of the Copenhagen Psychosocial Questionnaire (COPSOQ) using the question "To what extent do the demands of your work interfere with your private and family life?"…”
Section: Follow-up Questionnairementioning
confidence: 99%
“…Although the entire working population was affected, the risk of workplace exposure to SARS-CoV-2 varied by occupation and industry and changed over the course of the pandemic. At the beginning of the pandemic, there was an increased risk of contracting SARS-CoV-2 or dying from COVID-19, especially for healthcare professionals [1,2], but also for employees in social care, transportation, waste collection, safety and security occupations, or agriculture [1][2][3][4][5]. Other workers, such as teachers, cooks, or bartenders, were at greater risk in later pandemic waves when schools and businesses reopened [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Beale et al found that these differences were partly due to differences in work-related close contacts (11) and Reuter et al found that the SARS-CoV-2 infection risk was generally twice as high for essential workers than for non-essential workers (9). Attendance at the workplace during the COVID-19 pandemic seems generally to be a risk factor for a SARS-CoV-2 infection (13,14). In line with these findings, some studies found that the possibility to work from home was associated with a lower infection risk (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…In this issue of the Scandinavian Journal of Work Environment and Health , the study by Eekhout and colleagues illustrates its usefulness ( 11 ). Based on over 200 000 workers with serological SARS-CoV-2 test results, the test-negative design was applied to identify occupations with increased risk for infections, while simultaneously talking into account potential confounders, such as socioeconomic position and household composition.…”
mentioning
confidence: 99%